Strategi Komprehensif Guru, Kepala Sekolah, dan Guru BK dalam Penanganan serta Pencegahan Bullying di Sekolah - Widya Mauliddiana; Muthia Hanania; Hilmiyani Bestari; Ananda Aprilia; Cleodora Nathania Edlyn Weran; Ratna Fitria (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
Bullying in schools is a serious problem that negatively impacts the psychological and social development of students. This study aims to comprehensively analyze the strategies implemented by teachers, principals, and Guidance and Counseling (BK) teachers in preventing and handling bullying, while also examining the integration of Just and Civilized Humanity values ​​into these practices. The method used was descriptive qualitative with data collection techniques in the form of semi-structured interviews, observation, and documentation. The research subjects included subject teachers, BK teachers, and curriculum staff at a secondary school. The results showed that in efforts to handle and prevent bullying, teachers implemented a two-way dialogic approach in conflict management and early detection of bullying behavior. In addition, BK teachers implemented empathy-based classical guidance services, individual counseling, and multistakeholder coordination. Meanwhile, the school developed an anti-bullying co-curricular program involving the Student Council (OSIS), the Student Representative Council (MPK), and a monitoring team. The main obstacles included low case reporting and the normalization of bullying behavior by students. This study recommends strengthening synergy between parties through a structured and sustainable integrated anti-bullying team.